Method of Assessment of Gamma (G) -Radiation Effects In Rats (Texas Journal of Multidisciplinary Studies, 2022)
The widespread use of nuclear energy for peaceful purposes in life, including the use of radiation in the treatment of many diseases, requires the study of the effects of light on the body. It is also noted that the liver is one of the organs sensitive to direct radiation exposure in the use of radiotherapy in tumors of the digestive system.